THE RESTORATION OF HYPOTHALAMIC SIGNALING SYSTEMS AS ONE OF THE CAUSES TO IMPROVE THE METABOLIC PARAMETERS IN BROMOCRYPTINE-TREATED RATS WITH NEONATAL MODEL OF DIABETES MELLITUS - Derkach, K V; Ivantsov, A O; Sukhov, I B; Shpakov, A O (T͡S︡itologii͡a, 2017)
One of the approaches to correct type 2 diabetes mellitus (T2DM) and its complications is the use of drug bromocryptine mesylate (BCM), a selective agonist of type 2 dopamine receptors (DA2R). At the same time, the efficiency and the mechanisms of action of BCM in treatment of severe forms of T2DM are not currently understood. The objective was to study the effect of four-week treatment of male rats with neonatal T2DM model using BCM (300 mg/kg/day) on their metabolic parameters and activity of the adenylyl cyclase signaling system (ACSS) in the hypothalamus. The BCM treatment restored glucose tolerance and its utilization by exogenous insulin, and normalized lipid metabolism by lowering the levels of triglycerides and atherogenic cholesterol increased in T2DM. In the hypothalamus of BCM-treated diabetic rats, the regulation of ACSS by agonists of type 4 melanocortin receptor (MC4R), DA2R and 1B-subtype serotonin receptor, and the expression of Mc4r gene encoding MC4R were restored. Meanwhile, the BCM treatment had no effect on plasma insulin level and insulin production by pancreatic b-cells. The obtained data indicate the significant prospects of BCM to treat severe forms of experimental T2DM, and show that the therapeutic potential of this drug includes its ability to restore the hypothalamic signaling systems sensitive to monoamines and peptide of the melanocortin family, which are responsible for the control of energy metabolism and insulin sensitivity.